2018
DOI: 10.1099/jmm.0.000781
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted rectal infections in a cohort of ‘men having sex with men’

Abstract: Sexually transmitted rectal infections are frequent and often asymptomatic among MSM. LGV prevalence is high in our country and there is increasing evidence of symptomless cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Other interesting data emerged from the comparison between the two chlamydial serovars: cells infected by chlamydial L2 serovar displayed a higher activation of effector caspases compared to cells infected with serovar D. This aspect could be potentially ascribed to a different and serovar-specific activation of apoptotic pathways. Moreover, this phenomenon could explain one of the reasons of the greater virulence and pathogenic capacity displayed by chlamydial L serovars during genital and extra-genital infections [4, 31]. In agreement with these data we also found that globally L serovar showed a higher lethal effect than D serovar at least in Caco-2 and HeLa cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other interesting data emerged from the comparison between the two chlamydial serovars: cells infected by chlamydial L2 serovar displayed a higher activation of effector caspases compared to cells infected with serovar D. This aspect could be potentially ascribed to a different and serovar-specific activation of apoptotic pathways. Moreover, this phenomenon could explain one of the reasons of the greater virulence and pathogenic capacity displayed by chlamydial L serovars during genital and extra-genital infections [4, 31]. In agreement with these data we also found that globally L serovar showed a higher lethal effect than D serovar at least in Caco-2 and HeLa cells.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, CT can be found also at extra-genital sites, as pharyngeal and rectal mucosa, especially in women and ‘men having sex with men’ (MSM) [3]. Specific distinct CT serovars (L1-L3) are associated with lymphogranuloma venereum (LGV), emerging in Europe and North America as a leading cause of proctitis and proctocolitis in MSM, in particular in HIV-positive patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we found that rectal infection with Mg was 15.3%, almost three times higher than rates reported from Shenzhen (5.4%) in 2014 [17], Italy (4.8%) [20] and Australia (8.9%) [18]. The prevalence of rectal Mg in HIV-positive MSM in this study was 4.8 times that reported in the US (30.6% vs. 6.4%) [21].…”
Section: Discussionmentioning
confidence: 54%
“…In this study, it was useful to calculate comparable mean read depths and the number of downselected read pairs among the spiked samples of L2b, as this demonstrates success in enrichment for LGV strains as they have become prevalent among MSM 23,25,27,28 . Phylogenetic analysis of the 94 reference genomes (of which 85 genomes were used to develop the RNA bait library) showed genome representation from all four C. trachomatis lineages (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a number of studies have shown that rectal infections outnumber those in the urogenital tract of women and are on the increase among MSM [23][24][25][26][27][28] . Although common, rectal C. trachomatis transmission and its impact on morbidity is not well understood, likely due to the lack of routine screening of populations other than MSM 1,22,29 .…”
Section: Introductionmentioning
confidence: 99%